2019
DOI: 10.1108/bfj-07-2019-0489
|View full text |Cite
|
Sign up to set email alerts
|

Extending the shelf-life of sponge cake by an optimized level of jujube fruit flour determined using custom mixture design

Abstract: Purpose Jujube fruit (JF) (Ziziphus jujuba Mill.) is used as pharmaceuticals food, flavors and food additives. The purpose of this paper is to study the suitability of JF incorporation into a commercial sponge cake formulation, and to produce a nutritious bakery product with appropriate organoleptic and technological characteristics. Design/methodology/approach The optimal level of JF was incorporated into sponge cake using a custom mixture design with three independent variables, namely, refined wheat flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In [101] a simplex-lattice design was used to formulate frying oils (from soybean, safflower and flaxseed oils) with high content of essential fatty acids and low n-6/n-3 ratio. Other studies have regarded the shelf-life of cakes and candies [23,102]. In [102], jujube flour was used to improve the shelf-life of sponge cakes and the results showed that using about 7% of the ingredient in partial substitution of sugar and refined wheat flour improved not only the shelf life of the product but even the textural and physicochemical properties.…”
Section: Mixture Design For the Study Of Shelf-life And Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In [101] a simplex-lattice design was used to formulate frying oils (from soybean, safflower and flaxseed oils) with high content of essential fatty acids and low n-6/n-3 ratio. Other studies have regarded the shelf-life of cakes and candies [23,102]. In [102], jujube flour was used to improve the shelf-life of sponge cakes and the results showed that using about 7% of the ingredient in partial substitution of sugar and refined wheat flour improved not only the shelf life of the product but even the textural and physicochemical properties.…”
Section: Mixture Design For the Study Of Shelf-life And Stabilitymentioning
confidence: 99%
“…Other studies have regarded the shelf-life of cakes and candies [23,102]. In [102], jujube flour was used to improve the shelf-life of sponge cakes and the results showed that using about 7% of the ingredient in partial substitution of sugar and refined wheat flour improved not only the shelf life of the product but even the textural and physicochemical properties. Spanemberg and colleagues [23] used a D-optimal design to determine the sugar formulation that maximizes the shelf life and critical moisture content of hard candy.…”
Section: Mixture Design For the Study Of Shelf-life And Stabilitymentioning
confidence: 99%
“…In bakery products, MDs have been used in functional milk [97], chocolate [94], pecan nut [101,102], and sponge [98] cake formulations; gluten-free formulation of bread [87,93] and cakes [88]; noodle [100] and rice bread [99] formulations; cake [89] and staple bread [95] formulation; cassava crackers enriched [96]; flour [91] and whole-food [90] blend formulation and cereal recipe [92].…”
Section: Application Of Mixture Design In Foodmentioning
confidence: 99%
“…Among the most frequent applications of MDs in bakery products are formulations of gluten-free products, such as the formulation of bread using sorghum flour, rice flour, and millet flour [87]; a gluten-free bread based on chickpea flour [93], and a gluten-free cake enriched with protein [88]. Other applications of MDs extend the incorporation of products with different purposes, such as inserting jujube flour in the sponge cake [98], the addition of tikhur starch as a substitute for semolina in the preparation of baked milk cake [97], formulation of chocolate cake with partial replacement of wheat flour with yacon and maca flour [94], formulation of cassava-fish crackers with a combination of ingredients such as cassava starch, high-quality cassava flour, and fish flour [96], formulation of rice noodles that include combinations of gelatinized corn starch, xanthan gum, and guar gum to improve the tensile strength of cooked noodles [100] and the formulation of a low-cost fiber-rich whole food from residues from the processing of orange juice [90].…”
Section: Application Of Mixture Design In Foodmentioning
confidence: 99%
“…Recent research on SCs mainly focusses on the evaluation of SC quality when including a variety of ingredients in the recipe such as pea protein (Bustillos, Jonchere, Garnier, Reguerre, & Della Valle, 2020), olive stone powder (Jahanbakhshi & Ansari, 2020) or broccoli leaf powder (Krupa-Kozak et al, 2019) or when replacing (part of the) flour by rice starch (Wang, Zhao, Liu, & Xiong, 2020), jujube fruit flour (Hosseini, Bolourian, & Shahidi, 2019) or Eucheuma powder (Huang & Yang, 2019). From the above, it is clear that novel fundamental studies on SC structure setting during baking are lacking.…”
Section: Introductionmentioning
confidence: 99%